Implementation of Sanger DNA Sequencing Technologies in Tracing the Phylogeny of Meliola mangiferae - Dar, Rafiq Ahmad; Rai, Akhila Nand (Edelweiss Applied Science and Technology, 2017)
During the summer 2014, dark black symptoms beneath the leaf surfaces were observed on the Populas alba L species in the south Kashmir. In the later stages of development the infection subtends the whole surface resulting in leaf collapse. Fungal isolates were recovered directly from the structures present on the lesions. Purified DNA from each isolate was amplified using the random amplified polymorphic DNA technique recruiting the ITSI (TCCGTAGGTGAACCTGCGG) and ITS4 (TCCTCCGC TTATTGATATGC) specific primers. Amplification products visualized on agarose gel showed specific band pattern for each isolate. The mycotaxonomic characterization and phylogenetic interpretations showed the emergence of fungal species, Meliola sp. KY623717 with genetic variance of 2% in internal transcribed spacer (ITS) region of rDNA from closely related species under geographically distinct region.